Adverse events in older patients undergoing ERCP: a systematic review and meta-analysis - Day, Lukejohn W.; Lin, Lisa; Somsouk, Ma (Endoscopy International Open, 2014)
Background and study aims: Biliary and pancreatic diseases are common in the elderly; however, few studies have addressed the occurrence of adverse events in elderly patients undergoing endoscopic retrograde cholangiopancreatography (ERCP). Our objective was to determine the incidence rates of specific adverse events in this group and calculate incidence rate ratios (IRRs) for selected comparison groups.Patients and methods: Bibliographical searches were conducted in Medline, EMBASE, and Cochrane library databases. The studies included documented the incidence of adverse events (perforation, pancreatitis, bleeding, cholangitis, cardiopulmonary adverse events, mortality) in patients aged ≥ 65 who underwent ERCP. Pooled incidence rates were calculated for each reported adverse event and IRRs were determined for available comparison groups. A parallel analysis was performed in patients aged ≥ 80 and ≥ 90.Results: Our literature search yielded 7429 articles, of which 69 studies met our inclusion criteria. Pooled incidence rates for adverse events (per 1000 ERCPs) in patients aged ≥ 65 were as follows: perforation 3.8 (95 %CI 1.8 – 7.0), pancreatitis 13.1 (95 %CI 11.0 – 15.5), bleeding 7.7 (95 %CI 5.7 – 10.1), cholangitis 16.1 (95 %CI 11.7 – 21.7), cardiopulmonary events 3.7 (95 %CI 1.5 – 7.6), and death 7.1 (95 %CI 5.2 – 9.4). Patients ≥ 65 had lower rates of pancreatitis (IRR 0.3, 95 %CI 0.3 – 0.4) compared with younger patients. Octogenarians had higher rates of death (IRR 2.4, 95 %CI 1.3 – 4.5) compared with younger patients, whereas nonagenarians had increased rates of bleeding (IRR 2.4, 95 %CI 1.1 – 5.2), cardiopulmonary events (IRR 3.7, 95 %CI 1.0 – 13.9), and death (IRR 3.8, 95 %CI 1.0 – 14.4).Conclusions ERCP appears to be safe in elderly patients, except in the very elderly who are at higher risk of some adverse events. These data on adverse event rates can help to inform clinical decision-making, the consent process, and comparative effectiveness analyses.